Fe3O4 enhanced efficiency of volatile fatty acids production in anaerobic fermentation of food waste at high loading. (November 2022) - Wang, Lanting; Lei, Zhongfang; Yang, Xiaojing; Zhang, Chi; Liu, Chang; Shimizu, Kazuya; Zhang, Zhenya; Yuan, Tian
Graphical abstract: Highlights: This study explored the approach to enhance VFAs yield with overloaded substrates. Fe3 O4 significantly enhanced VFAs production by 160% at a high S/I ratio of 3. Fe3 O4 enhanced hydrolysis of particulate/soluble organics, especially at S/I of 3. Fe3 O4 enhanced reproduction and diversity of hydrolytic and acidogenic bacteria. Fe3 O4 reduced the abundance of Lactobacillus at high loading of food waste. Abstract: High treatment capacity for food waste (FW) is required due to the huge amount generated worldwide. Conversion of FW to volatile fatty acids (VFAs) via anaerobic fermentation is a promising technology; however, inhibition of VFAs production could easily occur at high loadings. In this study, Fe3 O4 was used to enhance VFAs production in anaerobic fermentation of FW at high loading, and the mechanisms involved were revealed at microbial levels. Results showed that Fe3 O4 significantly enhanced VFAs yield and VFAs productivity of microbes by 160% at high loading (substrate to inoculum (S/I) ratio of 3). The enhancement effect of Fe3 O4 was mainly due to the accelerated hydrolysis of particulate/soluble organics, the enriched hydrolytic and acidogenic bacteria, and the reduced relative abundance of Lactobacillus . This study provides a new approach for the high-efficient treatment of FW at high loadings, while the performance and economic benefit should be further studied for practical application.